Stable Angina Medical Therapy Management Guidelines: A Critical Review of Guidelines from the European Society of Cardiology and National Institute for Health and Care Excellence - Talla A Rousan (Radcliffe Medical Media, 2019)
Most patients with stable angina can be managed with lifestyle changes, especially smoking cessation and regular exercise, along with taking antianginal drugs. Randomised controlled trials show that antianginal drugs are equally effective and none of them reduced mortality or the risk of MI, yet guidelines prefer the use of beta-blockers and calcium channel blockers as a first-line treatment. The European Society of Cardiology guidelines for the management of stable coronary artery disease provide classes of recommendation with levels of evidence that are well defined. The National Institute for Health and Care Excellence (NICE) guidelines for the management of stable angina provide guidelines based on cost and effectiveness using the terms first-line and second-line therapy. Both guidelines recommend using low-dose aspirin and statins as disease-modifying agents. The aim of this article is to critically appraise the guidelines’ pharmacological recommendations for managing patients with stable angina.